Simultaneous detection method of muscle developing five monoclonal antibodies in human plasma with using LC-MS/MS - 이현정; Hwang, Ji In; 서윤담; 강인선; 손정현; Hwa Jeong Lee; 민호필 (2023년도 제71회 한국분석과학회 추계 학술대회 초록집, 2023)
Skeletal muscle loss is a common issue in diseases like muscular dystrophy, type 2 diabetes, and cardiovascular conditions. Current treatments aim to slow down muscle degeneration using nutritional supplements and appetite stimulants. However, a promising approach for muscle wasting disorders involves targeting the receptor signaling of the transforming growth factor beta (TGFβ) superfamily, which includes myostatin, GDF-11, and activin A. These molecules act as inhibitors of skeletal muscle growth. Inhibiting the myostatin receptor signaling pathway has been found to increase muscle mass. It's important to note that using inhibitors of this pathway as potential performance-enhancing agents in sports is prohibited by the World Anti-Doping Agency (WADA). This study developed a multiplex detection method for five prohibited monoclonal antibodies used in doping, which target the TGFβ superfamily. A minimal 5？L of plasma was used, and immuno-affinity purification with protein G magnet beads helped reduce contaminants. An internal standard, dulaglutide, was used for quality control during sample preparation. The method involved capturing these antibodies and the internal standard, followed by tryptic digestion and LC-HRMS analysis to detect signature peptides from each antibody. The validation confirmed excellent specificity, identification capacity, linearity, precision, and accuracy. All five monoclonal antibodies had a limit of detection (LOD) below 1？g/mL. While anti-TGFβ superfamily antibodies lack clinical approval, this detection method is essential for doping control and can be adapted for other protein therapeutics.